2015
DOI: 10.2174/1389450116666150223163632
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Multifaceted HuR Protein, Benefits and Caveats

Abstract: The RNA-binding protein (RBP) HuR is one of the most widely studied regulators of the eukaryotic posttranscriptional gene expression and it plays a physiological role in mediating the cellular response to apoptotic, proliferating and survival stimuli. Following physiological or stress stimuli, HuR protein binds to Adenylate-Urydinilate rich elements (AREs) generally contained in the 3'UTR of transcripts, then it shuttles from the nucleus to the cytoplasm and regulates the half-life and/or translation of cargo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
61
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 177 publications
1
61
0
Order By: Relevance
“…CRC tumors have a disproportionate level of tumor promoting genes expressed that contain AREs within their 3′UTRs [33], and many of these mRNA transcripts have been shown to be bound and regulated by the RNA binding protein HuR [19]. Previous work in our lab demonstrated that cytoplasmic HuR localization is observed in 76% of colorectal adenomas and 94% of colorectal adenocarcinomas [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CRC tumors have a disproportionate level of tumor promoting genes expressed that contain AREs within their 3′UTRs [33], and many of these mRNA transcripts have been shown to be bound and regulated by the RNA binding protein HuR [19]. Previous work in our lab demonstrated that cytoplasmic HuR localization is observed in 76% of colorectal adenomas and 94% of colorectal adenocarcinomas [12].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, increased HuR expression and cytoplasmic localization in tumors correlate with poor disease prognosis and advanced tumor staging [12, 4851]. Thus, there are many data points from multiple laboratories over various tumor types that HuR is a strong candidate target in cancer [7, 18, 19, 52]. In this study, MS444 is used here as a tool compound for proof-of-principle for pharmacological HuR inhibition, and that targeting HuR with MS-444 has anti-tumor activity as a monotherapy in multiple pre-clinical models for CRC.…”
Section: Discussionmentioning
confidence: 99%
“…[13] This is the first application of pharmacological inhibition of HuR in cardiac myocytes, and given the high recent interest in developing a pharmacological inhibitor of HuR for therapeutic use [13,25-27], represents a potential means for long-term translation of these basic science findings. Importantly, HuR knockdown or inhibition in basal/resting NRVMs appears to have very little effect.…”
Section: Discussionmentioning
confidence: 99%
“…The human antigen R (HuR; or ELAV1) is a member of the embryonic lethal abnormal vision RNA-binding protein family, known to regulate the half-life of target mRNAs (17). Initially identified as an mRNA export factor (18), its main nuclear functions are regulation of splicing, mRNA processing, and polyadenylation (19).…”
Section: Introductionmentioning
confidence: 99%